Ductile–Brittle Transition Temperature of Epoxy Asphalt Concrete of Steel Bridge Deck Pavement Based on Impact Toughness - Shunxian Zhang; Wen Nie; Aimin Sha; Weixiong Li; Wei Jiang (Advances in Materials Science and Engineering)
To solve the common low-temperature cracking problem of epoxy asphalt concrete pavement on the steel bridge deck, based on the principle of fracture mechanics and energy method, this paper puts forward the impact toughness as the evaluation index of crack resistance of epoxy asphalt concrete and verifies the feasibility of this index through theoretical analysis and experiment. At the same time, based on the study of impact toughness, the ductile–brittle transition temperature of epoxy asphalt concrete was explored, and the working state of epoxy asphalt concrete at different temperatures was mastered. The results show that the impact toughness is closely related to the J integral, which can better evaluate the crack resistance of epoxy asphalt mixture. The Boltzmann function can accurately reflect the relationship between impact toughness and temperature and can determine the ductile–brittle transition temperature and transition interval of epoxy asphalt concrete. Impact toughness and ductile–brittle transition temperature can be used as the evaluation index of crack resistance of epoxy asphalt concrete, which provides a new design idea for the study of crack resistance of epoxy asphalt concrete and the scope of engineering application.